Intergrated Control of Corn Downy Mildew Using Trichoderma Asperellum and Curcuma Aeruginosa - Prasetyo, Joko; Aeny, Titik Nur; Rahmadanti, Tita Prenti; Efri, (European Journal of Applied Sciences, 2023)
This study aims to determine the effect of the spore density of Trichoderma asperellum and the concentration of Black Curcuma extract and their interaction on the intensity of downy mildew and the growth of maize. This research was conducted at the Integrated Field Laboratory of the Faculty of Agriculture and the Laboratory of Plant Diseases, Department of Agrotechnology, Faculty of Agriculture, University of Lampung from March 2019 to May 2019. The design used in this experiment was a randomized block design, which was arranged in factorial experiment. The first factor was the treatment of T. asperellum which consists of 3 levels, namely without T. asperellum (T0), T. asperellum with a spore density of 106 spores / mL (T1), and T. asperellum with a density of 108 spores / mL (T2), applied in rhizosphere. The second factor was the concentration of Black Curcuma (Curcuma aeruginosa) extract which consists of 4 levels, namely 0% (F0), 20% (F1), 40% (F2) and 60% (F3), applied at the growing point of corn. The variables observed were incubation period, disease incidence, disease severity, plant height and stover weight. The observational data obtained were analyzed using analysis of variance and then tested by the LSD test at the 5% level. The results showed that the treatment of T. asperellum density of 108 spores / mL can reduce the incidence and severity of downy mildew. Treatment of T. asperellum of the density of 106 spores / mL can increase the dry weight of plant shoots and T. aspereellum density of 108 spores / mL can increase the dry weight of plant roots. Treatment of Black Curcuma extract with a concentration of 40% can reduce disease incidence, disease severity and increase stover weight. The best density of T. asperellum in suppressing downy mildew disease was the density of 108 spores / mL and the best concentration of Black Curcuma extract in controlling downy mildew, namely a concentration of 40%.